Peningkatan Mufradat Bahasa Arab Siswa Kelas 7G MTsN 4 Sidoarjo Melalui Penggunaan Metode Crossword Puzzle Berbasis Apliksi Puzzle Maker - Firdausi, Anisah; Tazkiyah Auliya; Wulan Indah Fatimatul Djamilah; Nur Sjamsuarini Pudji Astutik (JBES (Journal Basic Education Skills), 2024)
This research is motivated by the lack of creativity of educators in teaching mufrodat to students in class, so that students who memorize new mufrodat related to the material being taught are easily forgotten and this results in a decrease in student learning outcomes. This research aims to determine the application of the crossword puzzle learning model by utilizing puzzle maker learning media to improve students' ability to memorize Arabic vocabulary. This research uses the type of classroom action research (PTK) with Kurt Lewin's PTK theory model which has four stages, namely planning, action, observation and reflection. The research subjects this time were 32 students in class VII G. This research was conducted using 2 meetings and a formative assessment was given. At the first meeting held on Monday, March 18 2024, learning using the lecture method and formative assessment at that meeting obtained an average score of 60.73 and at the second meeting using the Crossword method and obtained an average score of 98.12. By comparing these two averages, it is proven that there is an increase in the use of Crossword puzzle media with puzzle maker applications.